Stress control structure, preparation method and application in the preparation process of gallium nitride single crystal
By designing a stress-regulating structure during the preparation of GaN single wafer, using the stress covariant layer with gradual porosity to transfer and release stress, the problem of large mismatch stress accumulation in the preparation of GaN single wafer is solved, and high-quality GaN single crystal thin film and high yield thick film materials are achieved.
Patent Information
- Application Number
- CN202411114493.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-08-14
AI Technical Summary
In the prior art, there is a large mismatch stress accumulation during the preparation of gallium nitride single wafer, resulting in film fragmentation and low yield.
A stress control structure is designed during the preparation process of gallium nitride single-crystal chips. The stress covariant layers with the first increase in porosity and then decrease are superimposed in sequence to achieve stress transfer and release, and avoid the accumulation of large mismatch stresses.
The preparation of gallium nitride single crystal thin film template layers without cracks, low stress, low dislocation density, flat surface and high crystalline quality was achieved, and the yield and preparation efficiency of gallium nitride single crystal thick film materials were improved.
Smart Images

Figure CN118792738B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of semiconductor technology, and in particular to a stress regulating structure, a preparation method and an application in a gallium nitride single crystal wafer preparation process. Background Art
[0002] The wide bandgap semiconductor material gallium nitride (GaN) has a stable hexagonal wurtzite crystal structure with lattice constants a=0.31885nm, c=0.5185nm, and a-axis thermal expansion coefficient of 5.59×10 -6 K -1 , c-axis thermal expansion coefficient is 3.17×10 -6 K -1 Due to its wide direct band gap (E g 3.39eV), high breakdown field strength (E C 3-5 MVcm -1 ), large saturated electron drift velocity (υ sat 2.2×10 7 cms -1 ), high electron mobility (µ r Not less than 1000cm 2 V -1 s -1 ) and strong spontaneous polarization and piezoelectric polarization effects, which are not only suitable for the development of short-wavelength and long-wavelength optoelectronic devices (LED, LD, PD), but also suitable for the development of high-frequency, high-power microwave radio frequency devices and high-voltage, high-current power electronic devices.
[0003] However, since GaN cannot be grown into large-sized bulk single crystal materials by melting or solution methods, GaN single crystal materials are often prepared by heteroepitaxial growth using heterogeneous substrates. The earliest heterogeneous substrate used was sapphire single crystal substrate. Sapphire (α-Al 2 O 3 ) has a rhombohedral crystal structure, with a C-plane in-plane lattice constant of 0.476 nm and an in-plane thermal expansion coefficient of 7.5×10 - 6 K -1. Although there is a large lattice mismatch of 16% and a large thermal mismatch of -34% between sapphire and gallium nitride, the price of materials of the same size has dropped to the same level as silicon single crystal substrates due to the stability of sapphire at high temperatures and the continuous advancement of its single crystal preparation and growth technology. Based on this, the preparation of gallium nitride single crystal thin films using conventional metal organic chemical vapor deposition (MOCVD) and large mismatch heteroepitaxial growth on sapphire single crystal substrates is still the mainstream technical route for the preparation and production of gallium nitride-based light-emitting diode devices (LEDs). Hydride vapor phase epitaxy (HVPE) has fast growth rate and self-purification function, and is often used for the preparation and growth of gallium nitride single crystal thick film materials (thickness not less than 10μm) on sapphire single crystal substrates. When the HVPE epitaxial growth rate of gallium nitride single crystal thick film materials on sapphire single crystal substrates is faster than the rate at which line dislocations extend upward, the thicker the prepared gallium nitride single crystal thick film layer, the fewer line dislocations extend to the surface. When the thickness of the crack-free GaN film exceeds 100 μm, the dislocation density can be reduced to no more than 10 7 cm -2 By peeling off the sapphire single crystal substrate, a self-supporting gallium nitride single crystal thick film material can be obtained, and then through double-sided grinding and polishing, a gallium nitride single crystal wafer material for homoepitaxial preparation of gallium nitride devices can be prepared.
[0004] At present, the preparation of GaN single crystal thin film on sapphire substrate often adopts thin high-temperature aluminum nitride buffer layer or thin low-temperature gallium nitride buffer layer to regulate the large lattice mismatch stress and thermal mismatch stress of GaN on sapphire substrate. Among them, the aluminum nitride (AlN) buffer layer also has a hexagonal wurtzite structure, with lattice constants a=0.3112nm, c=0.4882nm; the a-axis thermal expansion coefficient is 4.15×10 - 6 K -1 , c-axis thermal expansion coefficient is 5.27×10 -6 K -1 Although the C-plane lattice constant of aluminum nitride (AlN) is higher than that of C-plane gallium nitride (GaN) and c-plane sapphire (α-Al 2 O 3 ) are smaller, and the in-plane thermal expansion coefficient is also smaller than that of C-plane gallium nitride (GaN) and c-plane sapphire (α-Al 2 O 3) are small. Based on the ultra-thin intermediate layer flexible substrate model, aluminum nitride is a relatively good large mismatch stress covariant intermediate layer for epitaxial gallium nitride on sapphire substrate. However, if the thickness of the thin aluminum nitride buffer layer is not appropriate and there is a strong bond between the sapphire substrate and the gallium nitride epitaxial layer, its large mismatch stress coordinated transfer effect cannot be effectively demonstrated. The large mismatch stress applied by the sapphire substrate to the gallium nitride epitaxial layer will still accumulate in the gallium nitride film layer, and the accumulated compressive stress increases significantly with the increase of the film thickness. When a certain critical thickness is exceeded, the accumulated compressive stress is released, causing the gallium nitride film layer to break. This is also the main reason why it is always difficult to improve the crack-free thickness and material yield of gallium nitride single crystal thick film materials directly prepared and grown on sapphire single crystal substrates using the HVPE process. If the dislocation density is to be further reduced and the crack-free thickness and material yield are to be improved, the preparation of gallium nitride single crystal thick film materials on sapphire single crystal substrates requires the design of new large mismatch stress regulation structures and the development of new methods for preparing self-supporting gallium nitride single crystal wafer materials. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In order to solve at least one of the above-mentioned technical problems in the preparation process of gallium nitride single crystal wafers in the prior art, the embodiments of the present invention provide a stress control structure, preparation method and application in the preparation process of gallium nitride single crystal wafers. By sequentially stacking stress-covariant layers whose porosity increases first and then decreases, it can provide a crack-free, low-stress, low-dislocation density, surface-flat and high-crystalline quality gallium nitride single crystal thin film template layer for the subsequent preparation of gallium nitride single crystal thick film epitaxial layer, and it is also easy to transfer the upper and lower large thermal mismatch compressive stresses generated in the large-scale cooling process after the preparation of the gallium nitride single crystal thick film epitaxial layer to the stress-covariant layer in sequence, and finally release them in a concentrated manner in the third ultra-thin porous aluminum nitride stress-covariant layer with the largest porosity and the thinnest thickness, so as to achieve complete decoupling and self-peeling of the sapphire single crystal substrate from the third ultra-thin porous aluminum nitride stress-covariant layer.
[0007] (II) Technical solution
[0008] In view of the above technical problems, embodiments of the present invention provide a stress control structure, a preparation method and an application in a gallium nitride single crystal wafer preparation process.
[0009] According to the first aspect of the present invention, a stress control structure for the preparation process of a gallium nitride single crystal wafer is provided, comprising: a sapphire single crystal substrate; a first target aluminum nitride single crystal thin film template layer, located on the sapphire single crystal substrate; a porous aluminum nitride stress covariant region, located on the side of the first target aluminum nitride single crystal thin film template layer away from the sapphire single crystal substrate; a second target aluminum nitride single crystal thin film template layer, located on the side of the porous aluminum nitride stress covariant region away from the sapphire single crystal substrate; and a gallium nitride single crystal thin film template layer, located on the side of the second target aluminum nitride single crystal thin film template layer away from the sapphire single crystal substrate. The porous aluminum nitride stress covariant region comprises a first porous aluminum nitride stress covariant layer, a second porous aluminum nitride stress covariant layer, a third porous aluminum nitride stress covariant layer, a fourth porous aluminum nitride stress covariant layer and a fifth porous aluminum nitride stress covariant layer, and the nanoporosity of each porous aluminum nitride stress covariant layer is not completely the same.
[0010] In some exemplary embodiments, the nanoporosity of the first porous aluminum nitride stress-cooperative layer is 10%-30%; the nanoporosity of the second porous aluminum nitride stress-cooperative layer is 30%-50%; the nanoporosity of the third porous aluminum nitride stress-cooperative layer is 50%-70%; the nanoporosity of the fourth porous aluminum nitride stress-cooperative layer is 30%-50%; and the nanoporosity of the fifth porous aluminum nitride stress-cooperative layer is 10%-30%.
[0011] In some exemplary embodiments, at least one of the following features is included: the thickness of the sapphire single crystal substrate is 300µm-1500µm; the thickness of the first target aluminum nitride single crystal thin film template layer is 300nm-500nm; the thickness of the first porous aluminum nitride stress-coherent layer is 30nm-50nm; the thickness of the second porous aluminum nitride stress-coherent layer is 20nm-30nm; the thickness of the third porous aluminum nitride stress-coherent layer is 10nm-20nm; the thickness of the fourth porous aluminum nitride stress-coherent layer is 20nm-30nm; the thickness of the fifth porous aluminum nitride stress-coherent layer is 30nm-50nm; the thickness of the second target aluminum nitride single crystal thin film template layer is 300nm-500nm; the thickness of the gallium nitride single crystal thin film template layer is 1000-5000nm.
[0012] In some exemplary embodiments, at least one of the following features is included: the dislocation density of the first target aluminum nitride single crystal thin film template layer is not higher than 1×10 8 cm -2 ; The surface roughness of the first target aluminum nitride single crystal thin film template layer is not higher than 0.5nm; The dislocation density of the second target aluminum nitride single crystal thin film template layer is not higher than 5×10 7 cm -2; The surface roughness of the second target aluminum nitride single crystal thin film template layer is not higher than 0.5nm; the dislocation density of the gallium nitride single crystal thin film template layer is not higher than 1×10 8 cm -2 ; The surface roughness of the gallium nitride single crystal thin film template layer is not higher than 0.5nm.
[0013] According to a second aspect of the present invention, a method for preparing a gallium nitride single crystal wafer is provided, comprising the following steps: preparing a sapphire single crystal substrate, baking and surface nitriding the sapphire single crystal substrate; sequentially preparing a first initial aluminum nitride single crystal thin film template layer, an aluminum indium nitride single crystal thin film region, and a second initial aluminum nitride single crystal thin film template layer on the sapphire single crystal substrate by a metal organic chemical vapor deposition process; thermally decomposing the indium component in the aluminum indium nitride single crystal thin film region by a first annealing process and precipitating it from the grain gaps and grain boundaries of the second initial aluminum nitride single crystal thin film template layer to obtain a porous nitride. The first initial aluminum nitride single crystal thin film template layer and the second initial aluminum nitride single crystal thin film template layer are subjected to a second annealing process to fuse, merge and recrystallize the grains in the first initial aluminum nitride single crystal thin film template layer and the second initial aluminum nitride single crystal thin film template layer to obtain a first target aluminum nitride single crystal thin film template layer and a second target aluminum nitride single crystal thin film template layer; a metal organic chemical vapor deposition process is used to prepare a gallium nitride single crystal thin film template layer on the second target aluminum nitride single crystal thin film template layer; the temperature is reduced to room temperature according to a first preset cooling rate, The gallium nitride single crystal thin film template layer is formed with the sapphire substrate to form a weak bond decoupling; a gallium nitride single crystal thick film epitaxial layer is prepared on the gallium nitride single crystal thin film template layer by using a hydride vapor phase epitaxy process; the temperature is lowered to room temperature according to a second preset cooling rate, so that the gallium nitride single crystal thick film epitaxial layer is completely self-peeled from the sapphire single crystal substrate; and the peeled gallium nitride single crystal thick film epitaxial layer is processed to obtain a gallium nitride single crystal wafer, wherein the aluminum indium nitride single crystal thin film region includes a first aluminum indium nitride single crystal thin film layer, a second aluminum indium nitride single crystal thin film layer, a third aluminum indium nitride single crystal thin film layer, and a fourth aluminum indium nitride single crystal thin film layer, which are prepared in sequence. The porous aluminum nitride stress covariance zone comprises a first porous aluminum nitride stress covariance layer, a second porous aluminum nitride stress covariance layer, a third porous aluminum nitride stress covariance layer, a fourth porous aluminum nitride stress covariance layer and a fifth porous aluminum nitride stress covariance layer which are prepared in sequence and the nanoporosity of each porous aluminum nitride stress covariance layer is not completely the same; and the dislocation density and surface flatness of the second target aluminum nitride single crystal film template layer are lower than those of the second initial aluminum nitride single crystal film template layer.
[0014] In some exemplary embodiments, at least one of the following features is included: the pressure of the first initial aluminum nitride single crystal thin film template layer prepared by the metal organic chemical vapor deposition process is 10Torr-30Torr and the temperature is 1100℃-1400℃; the pressure of the first aluminum indium nitride single crystal thin film layer prepared by the metal organic chemical vapor deposition process is 40Torr-60Torr and the temperature is 750℃-850℃; the pressure of the second aluminum indium nitride single crystal thin film layer prepared by the metal organic chemical vapor deposition process is 60Torr-80Torr and the temperature is 650℃-750℃; the pressure of the third aluminum indium nitride single crystal thin film layer prepared by the metal organic chemical vapor deposition process is 80Torr-100Torr and the temperature is 550℃-650℃; the metal organic chemical vapor deposition process is used to prepare The pressure of the fourth aluminum indium nitride single crystal thin film layer is 60Torr-80Torr, and the temperature is 650℃-750℃; the pressure of the fifth aluminum indium nitride single crystal thin film layer prepared by the metal organic chemical vapor deposition process is 40Torr-60Torr, and the temperature is 750℃-850℃; the pressure of the second initial aluminum nitride single crystal thin film template layer prepared by the metal organic chemical vapor deposition process is 10Torr-30Torr, and the temperature is 850℃-950℃; the pressure of the gallium nitride single crystal thin film template layer prepared by the metal organic chemical vapor deposition process is 50Torr-100Torr, and the temperature is 1000℃-1100℃; the pressure of the gallium nitride single crystal thick film epitaxial layer prepared by the hydride vapor phase epitaxy process is 100Torr-600Torr, and the temperature is 1000℃-1100℃.
[0015] In some exemplary embodiments, the first annealing process includes the following process parameters: the annealing atmosphere is a hydrogen atmosphere; the annealing pressure is 10 Torr-50 Torr; the annealing temperature is 1000° C.-1100° C.; and the annealing time is 0.5 h-3 h.
[0016] In some exemplary embodiments, the second annealing process includes the following process parameters: the annealing atmosphere is an ammonia atmosphere; the annealing pressure is 10 Torr-50 Torr; the annealing temperature is 1100° C.-1400° C.; and the annealing time is 0.5 h-5 h.
[0017] In some exemplary embodiments, the molar concentration of indium element in the first aluminum indium nitride single crystal thin film layer is 10%-30%; the molar concentration of indium element in the second aluminum indium nitride single crystal thin film layer is 30%-50%; the molar concentration of indium element in the third aluminum indium nitride single crystal thin film layer is 50%-70%; the molar concentration of indium element in the fourth aluminum indium nitride single crystal thin film layer is 30%-50%; and the molar concentration of indium element in the fifth aluminum indium nitride single crystal thin film layer is 10%-30%.
[0018] In some exemplary embodiments, the first preset temperature drop rate is not higher than 5° C. / min; and / or the second preset temperature drop rate is not lower than 15° C. / min.
[0019] According to a third aspect of the present invention, there is provided an application of a gallium nitride single crystal wafer prepared by any of the above methods, which can be applied to gallium nitride-based power electronic devices, gallium nitride-based microwave radio frequency devices, gallium nitride-based light emitting diode devices, gallium nitride-based laser diode devices and gallium nitride-based ultraviolet detection devices.
[0020] (III) Beneficial effects
[0021] It can be seen from the above technical solutions that the stress control structure, preparation method and application of the gallium nitride single wafer preparation process provided by the embodiment of the present invention have at least the following beneficial effects:
[0022] (1) The stress control structure of the gallium nitride single crystal wafer preparation process according to the embodiment of the present invention can not only provide a gallium nitride single crystal thin film template layer with no cracks, low stress, low dislocation density, smooth surface and high crystal quality for the subsequent preparation of the gallium nitride single crystal thick film epitaxial layer, but also can transfer the upper and lower large thermal mismatch compressive stresses generated in the large-scale cooling process after the preparation of the gallium nitride single crystal thick film epitaxial layer due to the fact that the thermal expansion coefficient of the aluminum nitride intermediate layer is smaller than that of sapphire and gallium nitride in sequence to each ultra-thin porous aluminum nitride stress covariant layer with a gradual nanoporosity, and finally transfer it to the third porous aluminum nitride stress covariant layer with the largest intermediate nanoporosity and the thinnest thickness for concentrated release.
[0023] (2) It is possible to achieve crack-free, low-stress, low-dislocation-density and high-crystalline quality preparation of GaN single crystal thick film epitaxial layers. By controlling the second preset cooling rate of rapid cooling, the sapphire single crystal substrate is completely decoupled and self-peeled from the third porous aluminum nitride stress covariant layer with the largest nanopore porosity and the thinnest thickness. It can effectively avoid the accumulation of large mismatch stress in the GaN single crystal thick film material layer, which is beneficial to improving the yield and preparation efficiency of self-supporting GaN single crystal thick film materials.
[0024] (3) By setting up the third porous aluminum nitride stress covariant layer with the highest nano-porosity and the thinnest thickness in the middle, the upper second initial aluminum nitride single crystal thin film template layer is weakly bonded and decoupled from the bottom first initial aluminum nitride single crystal thin film template layer and the sapphire single crystal substrate. This intermediate weakly bonded decoupled pore structure is beneficial to the fusion and recrystallization of the grains in the second initial aluminum nitride single crystal thin film template layer during high-temperature and high-vacuum annealing in an ammonia atmosphere, thereby obtaining a second target initial aluminum nitride single crystal thin film template layer with better crystal quality and surface flatness than the second initial aluminum nitride single crystal thin film template layer, laying a material foundation for the subsequent preparation and growth of gallium nitride single crystal thin film template layer with low stress and lower dislocation density by low-pressure metal organic chemical vapor deposition process. With the gallium nitride single crystal template layer with low stress and lower dislocation density, the subsequent gallium nitride single crystal thick film material hydride vapor phase epitaxy process can achieve low stress preparation and crack-free thickness, yield and preparation efficiency improvement, laying a foundation. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The above contents and other objects, features and advantages of the present invention will become more apparent through the following description of the embodiments of the present invention with reference to the accompanying drawings, in which:
[0026] Figure 1 A method for preparing a gallium nitride single crystal wafer according to an embodiment of the present invention is schematically shown;
[0027] Figure 2 The schematic diagram of the structure after sequentially preparing a first initial aluminum nitride single crystal thin film template layer, an aluminum indium nitride single crystal thin film region and a second initial aluminum nitride single crystal thin film template layer on a sapphire single crystal substrate according to an embodiment of the present invention is shown;
[0028] Figure 3 A stress regulating structure in a gallium nitride single wafer preparation process according to an embodiment of the present invention is schematically shown; and
[0029] Figure 4 The schematic diagram shows the structure before and after the temperature is lowered to room temperature according to the second preset cooling rate according to an embodiment of the present invention; wherein, Figure 4 (a) schematically shows a structural diagram before the temperature is lowered to room temperature at a second preset cooling rate according to an embodiment of the present invention; and Figure 4 (b) schematically shows a schematic diagram of the structure after the temperature is reduced to room temperature at a second preset cooling rate according to an embodiment of the present invention; and
[0030] Figure 5 The structural diagram of a gallium nitride single crystal wafer according to an embodiment of the present invention is schematically shown.
[0031] Description of reference numerals:
[0032] 1-sapphire single crystal substrate; 2-first initial aluminum nitride single crystal thin film template layer; 3-aluminum indium nitride single crystal thin film region; 31-first aluminum indium nitride single crystal thin film layer; 32-second aluminum indium nitride single crystal thin film layer; 33-third aluminum indium nitride single crystal thin film layer; 34-fourth aluminum indium nitride single crystal thin film layer; 35-fifth aluminum indium nitride single crystal thin film layer; 4-second initial aluminum nitride single crystal thin film template layer; 5-porous aluminum nitride stress covariant region; 51-first porous aluminum nitride stress covariant layer; 52-second porous aluminum nitride stress covariant layer; 53-third porous aluminum nitride stress covariant layer; 54-fourth porous aluminum nitride stress covariant layer; 55-fifth porous aluminum nitride stress covariant layer; 6-second target aluminum nitride single crystal thin film template layer; 7-gallium nitride single crystal thin film template layer; 8-gallium nitride single crystal thick film epitaxial layer; 9-first target aluminum nitride single crystal thin film template layer; 10-gallium nitride single crystal. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in combination with specific embodiments and with reference to the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The existing method for preparing a self-supporting gallium nitride single wafer is to first directly prepare and grow a strongly bonded aluminum nitride single crystal film or a low-temperature gallium nitride film on a sapphire single crystal substrate using a metal organic chemical vapor deposition process as a buffer layer, which is used to regulate the large mismatch stress of the gallium nitride single crystal film template layer epitaxially grown by the subsequent metal organic chemical vapor deposition process. The stress regulation effect of the gallium nitride single crystal film template layer is limited. On the gallium nitride single crystal film template layer on the sapphire substrate that accumulates a large mismatch stress, a gallium nitride single crystal thick film epitaxial layer is continuously prepared using a hydride vapor phase epitaxy process. The thicker the film layer, the greater the accumulated stress. The film layer is easily broken during the large temperature reduction process, the process of laser stripping the sapphire substrate, and the grinding and polishing process, which leads to a low material yield. For example, in order to avoid the film layer from breaking, the film layer thickness of the gallium nitride single crystal thick film to be prepared must be reduced. The prepared film layer thickness is thin, which not only fails to reduce the dislocation density, but also accumulates a large stress in the film layer. In this case, even if the self-supporting gallium nitride single crystal thick film material can be completely peeled off from the sapphire substrate, the large stress still accumulates in the film layer, causing the film layer to warp and the surface to be undulating, which is not suitable for the preparation of fine device structures and has low application value as a homogeneous gallium nitride substrate material.
[0035] Figure 1 A method for preparing a gallium nitride single crystal wafer according to an embodiment of the present invention is schematically shown.
[0036] like Figure 1 As shown, a method for preparing a gallium nitride single crystal wafer according to an embodiment of the present invention includes steps S110-S190.
[0037] In step S110, a sapphire single crystal substrate 1 is prepared, and baking and surface nitridation treatment are performed on the sapphire single crystal substrate 1. Optionally, the size of the sapphire single crystal substrate 1 includes a diameter of 2 inches, 4 inches, 6 inches, and 8 inches.
[0038] For example, a sapphire single crystal substrate 1 with a thickness of 300 μm-1500 μm is prepared and placed in a reaction chamber of a low-pressure metal organic chemical vapor deposition device; and the sapphire single crystal substrate 1 is subjected to high-temperature baking and surface nitridation treatment at 1000° C.-1200° C.
[0039] In step S120, a metal organic chemical vapor deposition process is used to sequentially prepare a first initial aluminum nitride single crystal thin film template layer 2, an aluminum indium nitride single crystal thin film region 3, and a second initial aluminum nitride single crystal thin film template layer 4 on a sapphire single crystal substrate 1. The aluminum indium nitride single crystal thin film region 3 includes a first aluminum indium nitride single crystal thin film layer 31, a second aluminum indium nitride single crystal thin film layer 32, a third aluminum indium nitride single crystal thin film layer 33, a fourth aluminum indium nitride single crystal thin film layer 34, and a fifth aluminum indium nitride single crystal thin film layer 35 that are sequentially prepared, and the molar concentration of indium element in each aluminum indium nitride single crystal thin film layer is not completely the same.
[0040] In some exemplary embodiments, the pressure of the first initial aluminum nitride single crystal thin film template layer 2 prepared by the metal organic chemical vapor deposition process is 10Torr-30Torr and the temperature is 1100℃-1400℃; the pressure of the first aluminum indium nitride single crystal thin film layer 31 prepared by the metal organic chemical vapor deposition process is 40Torr-60Torr and the temperature is 750℃-850℃; the pressure of the second aluminum indium nitride single crystal thin film layer 32 prepared by the metal organic chemical vapor deposition process is 60Torr-80Torr and the temperature is 650℃-750℃; the pressure of the third aluminum indium nitride single crystal thin film layer 34 prepared by the metal organic chemical vapor deposition process is 60Torr-80Torr and the temperature is 650℃-750℃; The pressure of the thin film layer 33 is 80Torr-100Torr, and the temperature is 550℃-650℃; the pressure of the fourth aluminum indium nitride single crystal thin film layer 34 prepared by the metal organic chemical vapor deposition process is 60Torr-80Torr, and the temperature is 650℃-750℃; the pressure of the fifth aluminum indium nitride single crystal thin film layer 35 prepared by the metal organic chemical vapor deposition process is 40Torr-60Torr, and the temperature is 750℃-850℃; the pressure of the second initial aluminum nitride single crystal thin film template layer 4 prepared by the metal organic chemical vapor deposition process is 10Torr-30Torr, and the temperature is 850℃-950℃.
[0041] In some exemplary embodiments, the molar concentration of indium element in the first aluminum indium nitride single crystal thin film layer 31 is 10%-30%; the molar concentration of indium element in the second aluminum indium nitride single crystal thin film layer 32 is 30%-50%; the molar concentration of indium element in the third aluminum indium nitride single crystal thin film layer 33 is 50%-70%; the molar concentration of indium element in the fourth aluminum indium nitride single crystal thin film layer 34 is 30%-50%; and the molar concentration of indium element in the fifth aluminum indium nitride single crystal thin film layer 35 is 10%-30%.
[0042] For example, on a sapphire single crystal substrate 1, a 10Torr-30Torr low-pressure metal organic chemical vapor deposition process is used to form a 300nm-500nm thick layer with a dislocation density of no more than 1×10 8 cm -2 and a first initial aluminum nitride single crystal thin film template layer 2 with a surface roughness not higher than 0.5 nm; on the first initial aluminum nitride single crystal thin film template layer 2, a 40 Torr-60 Torr low pressure metal organic chemical vapor deposition process is used to form a first aluminum indium nitride single crystal thin film layer 31 with a thickness of 30 nm-50 nm and a molar concentration of indium component of 10%-30% at a high temperature of 750° C.-850° C.; on the first aluminum indium nitride single crystal thin film layer 31, a 60 Torr A second aluminum indium nitride single crystal thin film layer 32 with a thickness of 20nm-30nm and a molar concentration of indium component of 30%-50% is formed at a high temperature of 650℃-750℃ by using a low-pressure metal organic chemical vapor deposition process of 80Torr-100Torr at a low temperature of 550℃-650℃. A third aluminum indium nitride single crystal thin film layer 33 having a molar concentration of 50%-70% is formed on the third aluminum indium nitride single crystal thin film layer 33; a fourth aluminum indium nitride single crystal thin film layer 34 having a thickness of 20nm-30nm and an indium component molar concentration of 30-50% is formed at a high temperature of 650-750°C by using a low pressure metal organic chemical vapor deposition process of 60Torr-80Torr; and a fourth aluminum indium nitride single crystal thin film layer 34 having a molar concentration of 40Torr-60Torr is formed on the fourth aluminum indium nitride single crystal thin film layer 34 by using a low pressure metal organic chemical vapor deposition process of 40Torr-60Torr. A fifth aluminum indium nitride single crystal thin film layer 35 with a thickness of 30nm-50nm and a molar concentration of indium component of 10%-30% is formed at a high temperature of 750℃-850℃ by a metal organic chemical vapor deposition process; and on the fifth aluminum indium nitride single crystal thin film layer 35, a second initial aluminum nitride single crystal thin film template layer 4 with a thickness of 300nm-500nm is formed at a high temperature of 850℃-950℃ by a low pressure metal organic chemical vapor deposition process of 10Torr-30Torr.
[0043] Figure 2The schematic diagram shows a structure diagram after sequentially preparing a first initial aluminum nitride single crystal thin film template layer 2, an aluminum indium nitride single crystal thin film region 3 and a second initial aluminum nitride single crystal thin film template layer 4 on a sapphire single crystal substrate 1 according to an embodiment of the present invention.
[0044] like Figure 2 As shown, the structure obtained in step S120 includes a sapphire single crystal substrate 1; a first initial aluminum nitride single crystal thin film template layer 2, located on the sapphire single crystal substrate 1; a first aluminum indium nitride single crystal thin film layer 31, located on the side of the first initial aluminum nitride single crystal thin film template layer 2 away from the sapphire single crystal substrate 1; a second aluminum indium nitride single crystal thin film layer 32, located on the side of the first aluminum indium nitride single crystal thin film layer 31 away from the sapphire single crystal substrate 1; a third aluminum indium nitride single crystal thin film layer 33, located on the side of the second aluminum indium nitride single crystal thin film layer 32 away from the sapphire single crystal substrate 1; a fourth aluminum indium nitride single crystal thin film layer 34, located on the side of the third aluminum indium nitride single crystal thin film layer 33 away from the sapphire single crystal substrate 1; a fifth aluminum indium nitride single crystal thin film layer 35, located on the side of the fourth aluminum indium nitride single crystal thin film layer 34 away from the sapphire single crystal substrate 1; and a second initial aluminum nitride single crystal thin film template layer 4, located on the side of the fifth aluminum indium nitride single crystal thin film layer 35 away from the sapphire single crystal substrate 1.
[0045] In step S130, the indium component in the aluminum-indium-nitrogen single crystal thin film region 3 is thermally decomposed by a first annealing process and precipitated from the grain gaps and grain boundaries of the second initial aluminum nitride single crystal thin film template layer 4, thereby obtaining a porous aluminum nitride stress covariant region 5, so that a weak bond decoupling is formed between the first initial aluminum nitride single crystal thin film template layer 2 and the second initial aluminum nitride single crystal thin film template layer 4. The porous aluminum nitride stress covariant region 5 includes a first porous aluminum nitride stress covariant layer 51, a second porous aluminum nitride stress covariant layer 52, a third porous aluminum nitride stress covariant layer 53, a fourth porous aluminum nitride stress covariant layer 54 and a fifth porous aluminum nitride stress covariant layer 55, which are prepared in sequence, and the nanoporosity of each porous aluminum nitride stress covariant layer is not completely the same.
[0046] In an embodiment of the present invention, by obtaining five porous aluminum nitride stress-coupling layers including a nanoporosity that first increases and then decreases, especially the third porous aluminum nitride stress-coupling layer 53 located in the middle position having the highest nanoporosity and the thinnest thickness, the upper second initial aluminum nitride single crystal thin film template layer 4 and the bottom first initial aluminum nitride single crystal thin film template layer 2 and the sapphire single crystal substrate 1 can be weakly bonded and decoupled.
[0047] For example, in a hydrogen atmosphere with a pressure of 10Torr-50Torr, the substrate is heated to 1000℃-1100℃ and high-temperature annealing is performed for 0.5 hour-3 hours to thermally decompose the indium component in the aluminum-indium-nitrogen single crystal thin film region 3 and precipitate from the grain gaps and grain boundaries of the second initial aluminum nitride single crystal thin film template layer 4 to form a porous aluminum nitride stress covariant region 5 containing nanopores and a gradual pore change, and to achieve weak bonding decoupling between the first initial aluminum nitride single crystal thin film template layer 2 and the second initial aluminum nitride single crystal thin film template layer 4.
[0048] In step S140, the grains in the first initial aluminum nitride single crystal thin film template layer 2 and the second initial aluminum nitride single crystal thin film template layer 4 are fused, combined and recrystallized by a second annealing process to obtain a first target aluminum nitride single crystal thin film template layer 9 and a second target aluminum nitride single crystal thin film template layer 6. The dislocation density and surface flatness of the second target aluminum nitride single crystal thin film template layer 6 are lower than those of the second initial aluminum nitride single crystal thin film template layer 4.
[0049] For example, in an ammonia atmosphere with a pressure of 10 Torr-50 Torr, the substrate is heated to 1100°C-1400°C and annealed at high temperature for 0.5 hour-5 hours, so that the grains in the weakly bonded and decoupled second initial aluminum nitride single crystal thin film template layer 4 are fused and recrystallized to form a dislocation density of no more than 5×10 7 cm -2 The second target aluminum nitride single crystal thin film template layer 6 has a high crystalline quality and a surface flatness not higher than 0.5 nm.
[0050] Due to the weak bonding decoupling between the second initial aluminum nitride single crystal thin film template layer 4 and the first initial aluminum nitride single crystal thin film template layer 2 and the sapphire single crystal substrate 1, by introducing the intermediate weak bonding decoupling pore structure and then performing high temperature and high vacuum annealing in an ammonia atmosphere, it is more conducive to the fusion, merging and recrystallization of the grains in the second initial aluminum nitride single crystal thin film template layer 4, thereby obtaining a second target aluminum nitride single crystal thin film template layer 6 with better crystal quality and surface flatness than the second initial aluminum nitride single crystal thin film template layer 4, laying a material foundation for the subsequent low-stress and lower dislocation density preparation and growth of the gallium nitride single crystal thin film template layer 7 by low-pressure metal organic chemical vapor deposition process. The gallium nitride single crystal thin film template layer 7 with low stress and lower dislocation density is conducive to the realization of low-stress preparation and crack-free thickness, yield and preparation efficiency improvement of the subsequent gallium nitride single crystal thick film material hydride vapor phase epitaxy process.
[0051] In some exemplary embodiments, the nanoporosity of the first porous aluminum nitride stress-cooperative layer 51 is 10%-30%; the nanoporosity of the second porous aluminum nitride stress-cooperative layer 52 is 30%-50%; the nanoporosity of the third porous aluminum nitride stress-cooperative layer 53 is 50%-70%; the nanoporosity of the fourth porous aluminum nitride stress-cooperative layer 54 is 30%-50%; and the nanoporosity of the fifth porous aluminum nitride stress-cooperative layer 55 is 10%-30%.
[0052] In step S150 , a gallium nitride single crystal thin film template layer 7 is prepared on the second target aluminum nitride single crystal thin film template layer 6 by using a metal organic chemical vapor deposition process.
[0053] For example, on the second target aluminum nitride single crystal thin film template layer 6 with high crystalline quality, a 50Torr-100Torr low pressure metal organic chemical vapor deposition process is used to form a 1000nm-5000nm thick single crystal aluminum nitride thin film with a dislocation density of no more than 1×10 8 cm -2 The gallium nitride single crystal thin film template layer 7 has a surface roughness not higher than 0.5 nm.
[0054] Figure 3 A stress regulating structure in a gallium nitride single wafer preparation process according to an embodiment of the present invention is schematically shown.
[0055] like Figure 3 As shown, the stress regulation structure obtained in step S150 includes: a sapphire single crystal substrate 1; a first target aluminum nitride single crystal thin film template layer 9, located on the sapphire single crystal substrate 1; a porous aluminum nitride stress covariance zone 5, located on the side of the first target aluminum nitride single crystal thin film template layer 9 away from the sapphire single crystal substrate 1; a second target aluminum nitride single crystal thin film template layer 6, located on the side of the porous aluminum nitride stress covariance zone 5 away from the sapphire single crystal substrate 1; and a gallium nitride single crystal thin film template layer 7, located on the side of the second target aluminum nitride single crystal thin film template layer 6 away from the sapphire single crystal substrate 1.
[0056] In some exemplary embodiments, the thickness of the sapphire single crystal substrate 1 is 300µm-1500µm; and / or the thickness of the first target aluminum nitride single crystal thin film template layer 9 is 300nm-500nm; and / or the thickness of the first porous aluminum nitride stress-compliant layer 51 is 30nm-50nm; and / or the thickness of the second porous aluminum nitride stress-compliant layer 52 is 20nm-30nm; and / or the thickness of the third porous aluminum nitride stress-compliant layer 53 is 10nm-20nm; and / or the thickness of the fourth porous aluminum nitride stress-compliant layer 54 is 20nm-30nm; and / or the thickness of the fifth porous aluminum nitride stress-compliant layer 55 is 30nm-50nm; and / or the thickness of the second target aluminum nitride single crystal thin film template layer 6 is 300nm-500nm; and / or the thickness of the gallium nitride single crystal thin film template layer 7 is 1000-5000nm.
[0057] The structure according to the embodiment of the present invention can provide a crack-free, low-stress, low-dislocation density, flat-surface, high-crystallization-quality gallium nitride single crystal thin film template layer 7 for the subsequent preparation of the gallium nitride single crystal thick film epitaxial layer 8, and can also easily transfer the upper and lower large thermal mismatch compressive stresses generated in the large-scale cooling process after the preparation of the gallium nitride single crystal thick film epitaxial layer 8 due to the smaller thermal expansion coefficient of the aluminum nitride intermediate layer than that of sapphire and gallium nitride to the porous aluminum nitride stress covariant regions 5 with gradually varying nano-porosity in sequence, and finally transfer to the third porous aluminum nitride stress covariant layer 53 with the largest intermediate nano-porosity and the thinnest thickness for centralized release. Not only is it easier to achieve the subsequent preparation of the gallium nitride single crystal thick film epitaxial layer 8 with crack-free, low-stress, low-dislocation density, and high-crystallization-quality, but also the sapphire single crystal substrate 1 can be completely decoupled and self-peeled from the third porous aluminum nitride stress covariant layer 53 with the largest intermediate nano-porosity and the thinnest thickness by controlling the second preset cooling rate of rapid cooling. It can effectively avoid the accumulation of large mismatch stress in the film layer of gallium nitride single crystal thick film material, which is beneficial to improving the yield and preparation efficiency of self-supporting gallium nitride single crystal thick film material.
[0058] In step S160, the temperature is lowered to room temperature at a first preset cooling rate to form a weak bond decoupling between the gallium nitride single crystal thin film template layer 7 and the sapphire single crystal substrate. Optionally, the first preset cooling rate is not higher than 5°C / min.
[0059] For example, the first preset cooling rate is regulated to slowly cool to room temperature, and the thermal mismatch compressive stress generated during the cooling process of the sapphire single crystal substrate 1 and the gallium nitride single crystal thin film template layer 7 is simultaneously transferred to the middle aluminum nitride stress covariant zone with a gradient nanopore density and concentrated in the third porous aluminum nitride stress covariant layer 53 with the highest nanopore density for release, and a crack-free, low-stress gallium nitride single crystal thin film template layer 7 that is weakly bonded and decoupled from the sapphire single crystal substrate 1 is obtained.
[0060] In step S170, a gallium nitride single crystal thick film epitaxial layer 8 is prepared on the gallium nitride single crystal thin film template layer 7 by using a hydride vapor phase epitaxy process. Figure 4 (a) in the figure.
[0061] For example, a low-stress, crack-free gallium nitride single crystal thin film template layer 7 that is weakly bonded and decoupled from a sapphire substrate is placed in a near-atmospheric-pressure hydride vapor phase epitaxy (HVPE) equipment reaction chamber, and a 100Torr-600Torr near-atmospheric-pressure hydride vapor phase epitaxy process is used on the gallium nitride single crystal thin film template layer 7 to prepare a gallium nitride single crystal thick film epitaxial layer 8 with a thickness of 500µm-5000µm at a high temperature of 1000°C-1100°C.
[0062] In step S180, the temperature is lowered to room temperature at a second preset cooling rate, so that the gallium nitride single crystal thick film epitaxial layer 8 is completely peeled off from the sapphire single crystal substrate 1. Optionally, the second preset cooling rate is not less than 15°C / min. Figure 4 (b) in the figure.
[0063] For example, the second preset cooling rate is regulated to quickly cool to room temperature, and the thermal mismatch compressive stress generated during the cooling of the sapphire single crystal substrate 1 and the gallium nitride single crystal thick film epitaxial layer 8 is simultaneously transferred to the porous aluminum nitride stress covariant zone 5 with a gradual nanopore density in the middle and concentrated in the third porous aluminum nitride stress covariant layer 53 with the highest nanopore density for release. The cooling process obtains a crack-free, warp-free, low-stress self-supporting gallium nitride single crystal thick film epitaxial layer 8 that is completely self-peeled off from the sapphire substrate.
[0064] In step S190, the stripped gallium nitride single crystal thick film epitaxial layer 8 is processed to obtain a gallium nitride single crystal wafer 10, see Figure 5 .
[0065] For example, the crack-free, warp-free, low-stress self-supporting gallium nitride single crystal thick film epitaxial layer 8 is cut, ground and polished, and the nanoporous aluminum nitride stress covariant layer with a gradient pore density and the gallium nitride single crystal thin film template layer 7 with a high defect density on the back are removed, and multiple sheets with a thickness of not less than 300 μm and a dislocation density of not more than 1×10 6 cm -2 A crack-free, warp-free, low-stress self-supporting gallium nitride single crystal wafer 10 with a surface roughness not higher than 0.5 nm.
[0066] The gallium nitride single crystal wafer 10 prepared according to the embodiment of the present invention can be applied to gallium nitride-based power electronic devices, gallium nitride-based microwave radio frequency devices, gallium nitride-based light emitting diode devices, gallium nitride-based laser diode devices and gallium nitride-based ultraviolet detection devices.
[0067] Embodiment 1:
[0068] A stress control structure for preparing a 4-inch self-supporting gallium nitride single crystal wafer, comprising:
[0069] The sapphire single crystal substrate 1 has a thickness of 1000 µm.
[0070] The first target aluminum nitride single crystal thin film template layer 9 has a thickness of 400 nm and a dislocation density of no more than 1×10 8 cm -2 The surface roughness is no greater than 0.5 nm and the substrate is located on a sapphire single crystal substrate 1 .
[0071] The first porous aluminum nitride stress-cooperative layer 51 , which has a thickness of 40 nm and contains 20% nanoporosity, is located on a side of the first target aluminum nitride single crystal thin film template layer 9 away from the sapphire single crystal substrate 1 .
[0072] The second porous aluminum nitride stress-compliant layer 52 , which has a thickness of 20 nm and contains 40% nanoporosity, is located on a side of the first porous aluminum nitride stress-compliant layer 51 away from the sapphire single crystal substrate 1 .
[0073] The third porous aluminum nitride stress-compliant layer 53 , which has a thickness of 10 nm and contains 60% nanoporosity, is located on a side of the second porous aluminum nitride stress-compliant layer 52 away from the sapphire single crystal substrate 1 .
[0074] The fourth porous aluminum nitride stress-compliant layer 54 , which has a thickness of 20 nm and contains 40% nanoporosity, is located on a side of the third porous aluminum nitride stress-compliant layer 53 away from the sapphire single crystal substrate 1 .
[0075] The fifth porous aluminum nitride stress-compliant layer 55 , which has a thickness of 40 nm and contains 20% nanoporosity, is located on a side of the fourth porous aluminum nitride stress-compliant layer 54 away from the sapphire single crystal substrate 1 .
[0076] The second target aluminum nitride single crystal thin film template layer 6 has a thickness of 400 nm and a dislocation density of 1×10 7 cm -2 The surface roughness is 0.5 nm and is located on the side of the fifth porous aluminum nitride stress-coherent layer 55 away from the sapphire single crystal substrate 1 .
[0077] Gallium nitride single crystal thin film template layer 7, thickness is 3000nm, dislocation density is 5×10 7 cm -2 The surface roughness is 0.5 nm and is located on the side of the second target aluminum nitride single crystal thin film template layer 6 away from the sapphire single crystal substrate 1 .
[0078] The porous aluminum nitride stress covariant region 5 with different nanoporosity is formed by complete thermal decomposition and separation of the indium component in the aluminum indium nitride single crystal thin film region 3 with different indium component concentrations.
[0079] A method for preparing a 4-inch self-supporting gallium nitride single crystal wafer comprises the following steps:
[0080] S1. Prepare a 4-inch sapphire single crystal substrate 1 with a thickness of 1000 µm and place it in a reaction chamber of a low-pressure metal organic chemical vapor deposition (MOCVD) device.
[0081] S2. The sapphire single crystal substrate 1 is baked at a high temperature of 1100° C. and subjected to surface nitridation treatment.
[0082] S3, on the sapphire single crystal substrate 1, a 30Torr low pressure metal organic chemical vapor deposition process is used to form a 400nm thick and 1×10 8 cm -2 And the first initial aluminum nitride single crystal thin film template layer 2 has a surface roughness of 0.5 nm.
[0083] S4. On the first initial aluminum nitride single crystal thin film template layer 2, a 50 Torr low pressure metal organic chemical vapor deposition process is used to form a first aluminum indium nitride single crystal thin film layer 31 with a thickness of 40 nm and a molar concentration of indium component of 20% at a high temperature of 800°C.
[0084] S5. On the first aluminum indium nitride single crystal thin film layer 31, a 70 Torr low pressure metal organic chemical vapor deposition process is used to form a second aluminum indium nitride single crystal thin film layer 32 with a thickness of 20 nm and a molar concentration of indium component of 40% at a medium high temperature of 700°C.
[0085] S6. On the second aluminum indium nitride single crystal thin film layer 32, a third aluminum indium nitride single crystal thin film layer 33 with a thickness of 10 nm and a molar concentration of indium component of 60% is formed at a medium-low temperature of 600°C by using a 90Torr low-pressure metal organic chemical vapor deposition process.
[0086] S7. On the third aluminum indium nitride single crystal thin film layer 33, a 70 Torr low pressure metal organic chemical vapor deposition process is used to form a fourth aluminum indium nitride single crystal thin film layer 34 with a thickness of 20 nm and a molar concentration of indium component of 40% at a medium high temperature of 700°C.
[0087] S8. On the fourth aluminum indium nitride single crystal thin film layer 34, a fifth aluminum indium nitride single crystal thin film layer 35 with a thickness of 40 nm and a molar concentration of indium component of 20% is formed at a high temperature of 800°C by using a 50 Torr low pressure metal organic chemical vapor deposition process.
[0088] S9. On the fifth aluminum indium nitride single crystal thin film layer 35, a second initial aluminum nitride single crystal thin film template layer 4 with a thickness of 400 nm is formed at a high temperature of 900°C by using a 20 Torr low pressure metal organic chemical vapor deposition process.
[0089] S10. In a 50Torr hydrogen atmosphere, the substrate is heated to 1100°C and annealed at high temperature for 1 hour to thermally decompose the indium component in the aluminum-indium-nitride single crystal thin film region 3 and precipitate from the grain gaps and grain boundaries of the second initial aluminum nitride single crystal thin film template layer 4 to form a porous aluminum nitride stress covariant region 5 containing nanopores and a gradual pore change, and to achieve weak bonding decoupling between the first initial aluminum nitride single crystal thin film template layer 2 and the second initial aluminum nitride single crystal thin film template layer 4.
[0090] S11, in a 50 Torr ammonia atmosphere, the substrate is heated to 1400°C and annealed at high temperature for 3 hours, and the grains in the weakly bonded and decoupled second initial aluminum nitride single crystal thin film template layer 4 are fused and recrystallized to form a dislocation density of 1×10 7 cm -2 The second target aluminum nitride single crystal thin film template layer 6 with high crystalline quality and a surface flatness of 0.5 nm, and the grains in the first initial aluminum nitride single crystal thin film template layer 2 are also fused, combined and recrystallized to form the first target aluminum nitride single crystal thin film template layer 9 with improved crystalline quality.
[0091] S12, on the second target aluminum nitride single crystal thin film template layer 6 with high crystalline quality, a 50Torr low-pressure metal organic chemical vapor deposition process is used to form a 3000nm thick and 5×10 7 cm -2 The gallium nitride single crystal thin film template layer 7 has a surface roughness of 0.5 nm.
[0092] S13, regulating the first cooling rate to 5°C / min and slowly cooling to room temperature, transferring the thermal mismatch compressive stress generated in the cooling process of the sapphire single crystal substrate 1 and the gallium nitride single crystal thin film template layer 7 to the porous aluminum nitride stress covariant region 5 with a gradual nanopore density in the middle and releasing it in the third porous aluminum nitride stress covariant layer 53 with the highest nanopore density, and taking out the crack-free, low-stress gallium nitride single crystal thin film template layer 7 that is weakly bonded and decoupled from the sapphire single crystal substrate 1.
[0093] S14. Place the low-stress, crack-free gallium nitride single crystal thin film template layer 7 that is weakly bonded and decoupled from the sapphire single crystal substrate 1 into a near-atmospheric-pressure hydride vapor phase epitaxy (HVPE) equipment reaction chamber, and grow a crack-free gallium nitride single crystal thick film epitaxial layer 8 with a thickness of 2000µm on the gallium nitride single crystal thin film template layer 7 using a 300Torr near-atmospheric-pressure hydride vapor phase epitaxy process at a high temperature of 1050°C.
[0094] S15, regulating the second cooling rate to 15°C / min to quickly cool down to room temperature, and transferring the thermal mismatch compressive stress generated in the cooling process of the sapphire single crystal substrate 1 and the gallium nitride single crystal thick film epitaxial layer 8 to the porous aluminum nitride stress covariant zone 5 with a gradual nanopore density in the middle and releasing it in the third porous aluminum nitride stress covariant layer 53 with the highest nanopore density. The layer is cooled and taken out to obtain a crack-free, warp-free, low-stress self-supporting gallium nitride single crystal thick film epitaxial layer 8 that is completely self-peeled off from the sapphire single crystal substrate 1.
[0095] S16, cutting, grinding and polishing the crack-free, warping-free, low-stress self-supporting gallium nitride single crystal thick film epitaxial layer 8, removing the ultra-thin aluminum nitride stress covariant layer containing some pore density gradient nanopores and the gallium nitride single crystal thin film template layer 7 with high defect density on the back, and processing to obtain three sheets of 500µm thick and dislocation density not higher than 1×10 6 cm -2 A crack-free, warp-free, low-stress self-supporting gallium nitride single crystal wafer 10 with a surface roughness not higher than 0.5 nm.
[0096] The 4-inch 500µm thick gallium nitride single crystal wafer 10 is used as a homogeneous substrate material to develop and produce a 5W output power gallium nitride-based laser device.
[0097] Embodiment 2:
[0098] A method for preparing a 6-inch self-supporting gallium nitride single crystal wafer comprises the following steps:
[0099] S1. Prepare a 6-inch sapphire single crystal substrate 1 with a thickness of 1500 µm, and place it in a reaction chamber of a low-pressure metal organic chemical vapor deposition (MOCVD) device.
[0100] S2. The sapphire single crystal substrate 1 is subjected to high temperature baking at 1100° C. and surface nitridation treatment.
[0101] S3, on the sapphire single crystal substrate 1, a 30Torr low pressure metal organic chemical vapor deposition process is used to form a 500nm thick and 1×10 8 cm -2 And the first initial aluminum nitride single crystal thin film template layer 2 has a surface roughness of 0.5 nm.
[0102] S4. On the first initial aluminum nitride single crystal thin film template layer 2, a first aluminum indium nitride single crystal thin film layer 31 with a thickness of 50 nm and a molar concentration of indium component of 30% is formed at a high temperature of 850°C by using a 60Torr low pressure metal organic chemical vapor deposition process.
[0103] S5. On the first aluminum indium nitride single crystal thin film layer 31, a second aluminum indium nitride single crystal thin film layer 32 with a thickness of 30 nm and a molar concentration of indium component of 50% is formed at a medium-high temperature of 750°C by using a 80Torr low-pressure metal organic chemical vapor deposition process.
[0104] S6. On the second aluminum indium nitride single crystal thin film layer 32, a 100 Torr low-pressure metal organic chemical vapor deposition process is used to form a third aluminum indium nitride single crystal thin film layer 33 with a thickness of 20 nm and a molar concentration of indium component of 70% at a medium-low temperature of 650°C.
[0105] S7. On the third aluminum indium nitride single crystal thin film layer 33, a fourth aluminum indium nitride single crystal thin film layer 34 with a thickness of 30 nm and a molar concentration of indium component of 50% is formed at a medium-high temperature of 770°C by using a 80Torr low-pressure metal organic chemical vapor deposition process.
[0106] S8. On the fourth aluminum indium nitride single crystal thin film layer 34, a fifth aluminum indium nitride single crystal thin film layer 35 with a thickness of 50 nm and a molar concentration of indium component of 30% is formed at a high temperature of 850°C by using a 60Torr low pressure metal organic chemical vapor deposition process.
[0107] S9. On the fifth aluminum indium nitride single crystal thin film layer 35, a second initial aluminum nitride single crystal thin film template layer 4 with a thickness of 500 nm is formed at a high temperature of 990°C by using a 30 Torr low pressure metal organic chemical vapor deposition process.
[0108] S10. In a 50Torr hydrogen atmosphere, the substrate is heated to 1200°C and annealed at high temperature for 2 hours to thermally decompose the indium component in the aluminum-indium-nitride single crystal thin film region 3 and precipitate from the grain gaps and grain boundaries of the second initial aluminum nitride single crystal thin film template layer 4 to form a porous aluminum nitride stress covariant region 5 containing nanopores and a gradual pore change, and to achieve weak bonding decoupling between the first initial aluminum nitride single crystal thin film template layer 2 and the second initial aluminum nitride single crystal thin film template layer 4.
[0109] S11, in a 50 Torr ammonia atmosphere, the substrate is heated to 1400°C and annealed at high temperature for 5 hours, and the grains in the weakly bonded and decoupled second initial aluminum nitride single crystal thin film template layer 4 are fused, combined and recrystallized to form a dislocation density of 1×10 7 cm -2 The second target aluminum nitride single crystal thin film template layer 6 with high crystalline quality and surface flatness of 0.5 nm is formed by the fusion and recrystallization of the grains in the first initial aluminum nitride single crystal thin film template layer 2 to form the first target aluminum nitride single crystal thin film template layer 9 with improved crystalline quality.
[0110] S12, on the second target aluminum nitride single crystal thin film template layer 6 with high crystalline quality, a 50 Torr low pressure metal organic chemical vapor deposition process is used to form a 5000 nm thick and 5×10 7 cm -2 The gallium nitride single crystal thin film template layer 7 has a surface roughness of 0.5 nm.
[0111] S13, regulating the first cooling rate to 3°C / min and slowly cooling to room temperature, transferring the thermal mismatch compressive stress generated in the cooling process of the sapphire single crystal substrate 1 and the gallium nitride single crystal thin film template layer 7 to the porous aluminum nitride stress covariant zone 5 with a gradual nanopore density in the middle and releasing it in the third porous aluminum nitride stress covariant layer 53 with the highest nanopore density, and taking out the crack-free and low-stress gallium nitride single crystal thin film template layer 7 that is weakly bonded and decoupled from the sapphire single crystal substrate 1.
[0112] S14, placing the low-stress crack-free gallium nitride single crystal thin film template layer 7 that is weakly bonded and decoupled from the sapphire single crystal substrate 1 into the reaction chamber of a near-atmospheric-pressure hydride vapor phase epitaxy (HVPE) device, and on the gallium nitride single crystal thin film template layer 7, using a 500Torr near-atmospheric-pressure hydride vapor phase epitaxy process at a temperature of 1050°C to grow a gallium nitride single crystal thick film epitaxial layer 8 with a thickness of 3000µm.
[0113] S15, regulating the second cooling rate to 20°C / min to quickly cool down to room temperature, and transferring the thermal mismatch compressive stress generated in the cooling process of the sapphire single crystal substrate 1 and the gallium nitride single crystal thick film epitaxial layer 8 to the porous aluminum nitride stress covariant zone 5 with a gradual nanopore density in the middle and releasing it in the third porous aluminum nitride stress covariant layer 53 with the highest nanopore density. The layer is cooled and taken out to obtain a crack-free, warp-free, low-stress self-supporting gallium nitride single crystal thick film epitaxial layer 8 that is completely self-peeled off from the sapphire single crystal substrate 1.
[0114] S16, cutting, grinding and polishing the crack-free, warping, low-stress self-supporting gallium nitride single crystal thick film epitaxial layer 8, removing the ultra-thin aluminum nitride stress covariant layer containing some pore density gradient nanopores on the back and the gallium nitride single crystal thin film template layer 7 with high defect density, and processing to obtain 5 sheets with a thickness of 500µm and a dislocation density of 5×10 5 cm -2 A crack-free, warp-free, low-stress gallium nitride single crystal wafer 10 with a surface roughness of 0.5 nm.
[0115] The 6-inch gallium nitride single crystal wafer 10 with a thickness of 500 µm is used as a homogeneous substrate material to develop and produce a high-voltage gallium nitride-based power electronic device with a withstand voltage of 3300V.
[0116] The above specific embodiments further illustrate the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A stress control structure for a gallium nitride single crystal wafer preparation process, characterized in that: include: Sapphire single crystal substrate; A first target aluminum nitride single crystal thin film template layer is located on the sapphire single crystal substrate; A porous aluminum nitride stress covariant region is located on a side of the first target aluminum nitride single crystal thin film template layer away from the sapphire single crystal substrate; A second target aluminum nitride single crystal thin film template layer is located on a side of the porous aluminum nitride stress covariant region away from the sapphire single crystal substrate; as well as a gallium nitride single crystal thin film template layer, located on a side of the second target aluminum nitride single crystal thin film template layer away from the sapphire single crystal substrate, The porous aluminum nitride stress covariant region includes a first porous aluminum nitride stress covariant layer, a second porous aluminum nitride stress covariant layer, a third porous aluminum nitride stress covariant layer, a fourth porous aluminum nitride stress covariant layer and a fifth porous aluminum nitride stress covariant layer which are sequentially arranged, and the nanoporosity of each porous aluminum nitride stress covariant layer is not completely the same. The nanoporosity of the first porous aluminum nitride stress-covariant layer is 10%-30%; The nanoporosity of the second porous aluminum nitride stress-covariant layer is 30%-50%; The nanoporosity of the third porous aluminum nitride stress covariant layer is 50%-70%; The nanoporosity of the fourth porous aluminum nitride stress-cooperative layer is 30%-50%; and The nanoporosity of the fifth porous aluminum nitride stress-cooperative layer is 10%-30%.
2. The stress control structure for the gallium nitride single crystal wafer preparation process according to claim 1, characterized in that: Includes at least one of the following features: The thickness of the sapphire single crystal substrate is 300µm-1500µm; The thickness of the first target aluminum nitride single crystal thin film template layer is 300nm-500nm; The thickness of the first porous aluminum nitride stress-covariant layer is 30nm-50nm; The thickness of the second porous aluminum nitride stress-coherent layer is 20nm-30nm; The thickness of the third porous aluminum nitride stress-cooperative layer is 10nm-20nm; The thickness of the fourth porous aluminum nitride stress-coherent layer is 20nm-30nm; The thickness of the fifth porous aluminum nitride stress-cooperative layer is 30nm-50nm The thickness of the second target aluminum nitride single crystal thin film template layer is 300nm-500nm; The thickness of the gallium nitride single crystal thin film template layer is 1000-5000nm.
3. The stress control structure in the gallium nitride single crystal wafer preparation process according to claim 1, characterized in that: Includes at least one of the following features: The dislocation density of the first target aluminum nitride single crystal thin film template layer is not higher than 1×10 8 cm -2 ; The surface roughness of the first target aluminum nitride single crystal thin film template layer is not higher than 0.5 nm; The dislocation density of the second target aluminum nitride single crystal thin film template layer is not higher than 5×10 7 cm -2 ; The surface roughness of the second target aluminum nitride single crystal thin film template layer is not higher than 0.5 nm; The dislocation density of the gallium nitride single crystal thin film template layer is not higher than 1×10 8 cm -2 ; The surface roughness of the gallium nitride single crystal thin film template layer is not higher than 0.5 nm.
4. A method for preparing a gallium nitride single crystal wafer, characterized in that: The following steps are involved: Preparing a sapphire single crystal substrate, and performing baking and surface nitriding treatment on the sapphire single crystal substrate; A first initial aluminum nitride single crystal thin film template layer, an aluminum indium nitrogen single crystal thin film region and a second initial aluminum nitride single crystal thin film template layer are sequentially prepared on the sapphire single crystal substrate by using a metal organic chemical vapor deposition process; Thermally decomposing the indium component in the aluminum-indium-nitride single crystal thin film region through a first annealing process and precipitating it from the grain gaps and grain boundaries of the second initial aluminum nitride single crystal thin film template layer to obtain a porous aluminum nitride stress covariant region, so that a weak bonding decoupling is formed between the first initial aluminum nitride single crystal thin film template layer and the second initial aluminum nitride single crystal thin film template layer; Through a second annealing process, the grains in the first initial aluminum nitride single crystal thin film template layer and the second initial aluminum nitride single crystal thin film template layer are fused, combined and recrystallized to obtain a first target aluminum nitride single crystal thin film template layer and a second target aluminum nitride single crystal thin film template layer; preparing a gallium nitride single crystal thin film template layer on the second target aluminum nitride single crystal thin film template layer by using a metal organic chemical vapor deposition process; Lowering the temperature to room temperature at a first preset cooling rate so that the gallium nitride single crystal thin film template layer and the sapphire single crystal substrate form a weak bond decoupling; Using a hydride vapor phase epitaxy process, a gallium nitride single crystal thick film epitaxial layer is prepared on the gallium nitride single crystal thin film template layer; Lowering the temperature to room temperature at a second preset cooling rate so that the gallium nitride single crystal thick film epitaxial layer is completely self-stripped from the sapphire single crystal substrate; and processing the stripped gallium nitride single crystal thick film epitaxial layer to obtain a gallium nitride single crystal wafer, The aluminum indium nitride single crystal thin film region includes a first aluminum indium nitride single crystal thin film layer, a second aluminum indium nitride single crystal thin film layer, a third aluminum indium nitride single crystal thin film layer, a fourth aluminum indium nitride single crystal thin film layer and a fifth aluminum indium nitride single crystal thin film layer which are prepared in sequence, and the molar concentration of indium element in each aluminum indium nitride single crystal thin film layer is not completely the same; The porous aluminum nitride stress-cooperative region includes a first porous aluminum nitride stress-cooperative layer, a second porous aluminum nitride stress-cooperative layer, a third porous aluminum nitride stress-cooperative layer, a fourth porous aluminum nitride stress-cooperative layer and a fifth porous aluminum nitride stress-cooperative layer which are prepared in sequence, and the nanoporosity of each porous aluminum nitride stress-cooperative layer is not completely the same; and The dislocation density and surface flatness of the second target aluminum nitride single crystal thin film template layer are lower than those of the second initial aluminum nitride single crystal thin film template layer. Wherein, the molar concentration of indium element in the first aluminum indium nitrogen single crystal thin film layer is 10%-30%; The molar concentration of indium element in the second aluminum indium nitrogen single crystal thin film layer is 30%-50%; The molar concentration of indium element in the third aluminum indium nitride single crystal thin film layer is 50%-70%; The molar concentration of indium element in the fourth aluminum indium nitride single crystal thin film layer is 30%-50%; and The molar concentration of indium element in the fifth aluminum indium nitride single crystal thin film layer is 10%-30%.
5. The preparation method according to claim 4, characterized in that: Includes at least one of the following features: The pressure of preparing the first initial aluminum nitride single crystal thin film template layer by metal organic chemical vapor deposition process is 10 Torr-30 Torr and the temperature is 1100° C.-1400° C.; The pressure of preparing the first aluminum indium nitrogen single crystal thin film layer by metal organic chemical vapor deposition process is 40 Torr-60 Torr and the temperature is 750° C.-850° C.; The pressure of preparing the second aluminum indium nitrogen single crystal thin film layer by metal organic chemical vapor deposition process is 60 Torr-80 Torr and the temperature is 650° C.-750° C.; The pressure of preparing the third aluminum indium nitrogen single crystal thin film layer by metal organic chemical vapor deposition process is 80 Torr-100 Torr and the temperature is 550° C.-650° C.; The fourth aluminum indium nitrogen single crystal thin film layer is prepared by a metal organic chemical vapor deposition process at a pressure of 60 Torr-80 Torr and a temperature of 650° C.-750° C.; The metal organic chemical vapor deposition process is used to prepare the fifth aluminum indium nitrogen single crystal thin film layer at a pressure of 40 Torr-60 Torr and a temperature of 750° C.-850° C.; The pressure of preparing the second initial aluminum nitride single crystal thin film template layer by metal organic chemical vapor deposition process is 10 Torr-30 Torr and the temperature is 850° C.-950° C.; The pressure of preparing the gallium nitride single crystal thin film template layer by metal organic chemical vapor deposition process is 50 Torr-100 Torr and the temperature is 1000° C.-1100° C.; The pressure of preparing the gallium nitride single crystal thick film epitaxial layer by the hydride vapor phase epitaxy process is 100 Torr-600 Torr and the temperature is 1000° C.-1100° C.
6. The preparation method according to claim 4, characterized in that: The first annealing process includes the following process parameters: The annealing atmosphere is a hydrogen atmosphere; Annealing pressure is 10Torr-50Torr; The annealing temperature is 1000°C-1100°C; and Annealing time is 0.5h-3h; and / or The second annealing process includes the following process parameters: The annealing atmosphere is an ammonia atmosphere; Annealing pressure is 10Torr-50Torr; The annealing temperature is 1100°C-1400°C; and The annealing time is 0.5h-5h.
7. The preparation method according to claim 4, characterized in that: The first preset cooling rate is not higher than 5°C / min; and / or The second preset cooling rate is not less than 15°C / min.
8. An application of a gallium nitride single crystal wafer prepared by the method according to any one of claims 4 to 7, characterized in that: It is applied to at least one of gallium nitride-based power electronic devices, gallium nitride-based microwave radio frequency devices, gallium nitride-based light emitting diode devices, gallium nitride-based laser diode devices and gallium nitride-based ultraviolet detection devices.
Citation Information
Patent Citations
Method for preparing aluminum nitride single crystal material
CN102828251A
Method for producing vertical-structured GaN-based light emitting diode by adopting sapphire substrate
CN103633199A